Mędrzec – ideał człowieka poszukującego mądrości (Syr 14,20 – 15,10). Część II: Działanie mądrości i przestroga skierowana do grzesznika (Syr 15,1-10) - Piwowar, Andrzej (The Biblical Annals, 2016)
The second part of Sir 14:20–15:10, that is 15:1-10, consists of five sections: 15:1 functions as an introduction, vv. 2-3 focus on wisdom’s actions towards the one who seeks it, vv. 4-6 contain promises made to the person who has acquired wisdom, vv. in turn 7-8 constitute a warning for the fool – that is the sinner, while in the concluding part of the pericope analyzed in the present article (vv. 9-10) Sirach speaks of God’s worship as the culmination of the efforts made in order to acquire wisdom. Mere intellectual efforts do not suffice to acquire wisdom. It is wisdom itself that helps those who seek to attain it (vv. 2-3; the metaphors of the mother and wife, of being fed the bread of knowledge and the water of wisdom). Wisdom is personified as the guide in the process while at the same time remaining the object being sought. Its actions towards the man who strives to acquire it are akin to God’s actions towards Israel and all the believers. The promises made in 15:4-6 pertain both to the wisdom-seeker’s earthly existence (he will never fall nor will he be disgraced; on the contrary, he will be elevated and awarded with joy) and his afterlife (his descendants will remember him forever). In 15:7-8 Sirach expresses a warning directed to fools, that is sinners. They will never attain wisdom for their conduct defies wisdom’s requirements for those who seek it (fear of God, knowledge of the Law and contemplation both of wisdom and the commandments). The author concludes by saying that God’s worship constitutes the apex of attaining wisdom, a sign that one has actually acquired it. Fools and sinners cannot worship God for they do not submit to God’s command and hence will never acquire wisdom. The article also compares the theological message of 14:20–15:10 concerning wisdom with other fragments of the Book of Sirach that refer to the seeking and finding of wisdom (1:1-10; 4:11-19 and 6:18-37).